Reinstating the Inherent Dignity of Marginalized Communities in Ghana - Afra Boateng, Anabella (Journal of Interdisciplinary Studies in Education, 2020)
When a representative democracy implicitly or explicitly undermines minority rights and prevents marginalized people from actively participating in a democratic process, it facilitates social exclusion. This paper focuses on how Ghana’s democracy, coupled with traditions, aggravate social exclusion. The research discusses the democratization process of Ghana and its role in the marginalization of minorities. Particularly, this paper looks at the class-based marginalization of women on the one hand and the sex-based marginalization of the LGBTQI+ community on the other, in Ghana. Finally, this paper explores how Soka Education, as a way of life, can support these marginalized communities in Ghana.